Between utopia and skepticism: the potential of virtual diaries in the national communication market - Tavernari, Mariana Della Dea (RuMoRes, 2008)
Web diaries are key elements for us to understand how optimistic and pessimistic prophecies are articulated in consequence of the emergence of new media and models in the national communication market. Under the perspective of comfort, they present themselves as an alternative to the unilaterality imposed by the traditional media. It is introduced an expressive narrative similar to the literary journalism anchored in the bilateral and interconnected environment of the internet and so they become the main target of the enthusiasts, the ones that idealize the so called communitarian journalism. Entre a utopia e o ceticismo: as potencialidades dos diários virtuais no mercado de comunicação nacional